Synthesis and Characterization of New Trinuclear Palladium(II) and Platinum(II) Complexes Containing Phosphorus-Sulphur Ligands - H. Buttrus, Nabeel; K. Hussain, Adil; A.K. Al-Allaf, Talal (Asian Journal of Chemistry, 2010)
Some new homo and hetero trinuclear Pd(II) and Pt(II) complexes with tridentate hybrid ligands containing phosphorus-sulphur species, of the general formula [MnM3-n L2CI6], where M = M' = Pt or Pd, n = 3; M = Pt, M' = Pd, n = 1 or 2 and L = cis- 1,2-bis(diphenylphosphino) phenylthioethylene (L1) or cis-1,2-bis (diphenylphosphino)-2-aminophenylthio ethylene (L2), have been synthesized and characterized physico-chemically and spectroscopically. The structures of the complexes have been elucidated on the basis of their elemental analyses, electronic and infrared spectral measurements.